Effect of Cryopreserved Placental Explants on Female Reproductive System Under Normal and Pathological Conditions (Experimental study) - Prokopyuk, Volodymyr Yu.; Grischenko, Olga V.; Prokopyuk, Oleksandra V.; Shevchenko, Nadiia O.; Falko, Oksana V.; Storchak, Anna V.; Schedrov, Andrii O. (Problems of Cryobiology and Cryomedicine, 2017)
One of the most important tasks in current medicine is the preservation and restoration of fertility. The application of human placental derivatives (mesenchymal stromal cells, fetal membranes, extracts and explants), having a high proliferative potential and the affinity to female reproductive system, is a promising direction for treating female reproductive pathology. Here we determined the effect of cryopreserved placental explants on female reproductive system under normal condi-tions (fertility and estral cycle) and in pathology (infectious process, endocrinopathy, autoimmune pathology, trauma/ischemia). The cryopreserved placental explants were revealed to have a trophic effect on uterus and ovaries, they temporarily delayed ovulation and positively affected autoimmune, endocrine pathology and ischemia course. In addition, placental explants aggravated the infection course and increased the peritoneal adhesion formation. Probl Cryobiol Cryomed 2017; 27(3): 250–265